FRAUD DIAMOND DAN KECURANGAN PELAPORAN KEUANGAN PADA SAAT SEBELUM DAN SAAT COVID-19 DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Hastuti, Indhi; Dewayanto, Totok (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2022)
The phenomenon that is currently happening is covid-19, in this research the researcher wanted to know before and during covid-19 whether there was fraud in financial reporting by using fraud diamonds to detect the fraud. The sample used is a manufacturing company with a period of 2018 - 2020.This study uses the independent variable external pressure for DAR proxy, financial target for ROA proxy, nature of industry for Inventory proxy, change in auditor and change in director. Good corporate governance is also used in this study as a moderating variable. The data processing used by the researcher is SPSS version 20.0. The results of this study indicate that the independent variable external pressure has an influence on fraudulent financial reporting either before or during covid-19 and also when using moderating variables.